2014
DOI: 10.7897/2277-4572.034154
|View full text |Cite
|
Sign up to set email alerts
|

Punarjanma (Reincarnation): A Bird Eye View

Abstract: Punarjanma (Reincarnation) is an interesting topic which evokes the curiousity of the researchers to explore the hidden truth behind this concept. The Karya Karana Siddhantha (cause -effect theory) has its limitation in certain diseases in which karana (cause) is not possible to elicit. There comes the role of the invisible factor termed Daiva (fate/predetermined) which is an outcome of one's past life deeds. The concept of Jatismara (claimed memories of previous life) clearly substantiates the truth behind Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The protein with PDB ID-5C5A was docked with the ligands and the standard drug, megestrol acetate. The results showed that the protein has considerable interaction with the ligands as tabulated in Table-8. The interpretation of result clearly confirms that ligands α-elemene, (-) γ-elemene, ar-turmerone, (-) β-elemene, demethoxycurcumin, ar-turmerone, bisdemethoxycurcumin showed considerably good docking results, except curcubitacin E. All the ligands were docked with the protein selected and compared to the standard drug, megestrol acetate by its docking score [23].…”
Section: Molecular Docking Analysissupporting
confidence: 63%
“…The protein with PDB ID-5C5A was docked with the ligands and the standard drug, megestrol acetate. The results showed that the protein has considerable interaction with the ligands as tabulated in Table-8. The interpretation of result clearly confirms that ligands α-elemene, (-) γ-elemene, ar-turmerone, (-) β-elemene, demethoxycurcumin, ar-turmerone, bisdemethoxycurcumin showed considerably good docking results, except curcubitacin E. All the ligands were docked with the protein selected and compared to the standard drug, megestrol acetate by its docking score [23].…”
Section: Molecular Docking Analysissupporting
confidence: 63%
“…It includes the adoption of Yajna and homa (fire sacrifices), pooja (worship), Japa (enchanting), manidharana (wearing rings and beads, teing threads etc after worshipping), Upavasa (fasting), Prayaschitta (confessing) etc. 19 This considers the Karmic causes of diseases and their mitigation by means of spiritual alternatives. Thus Daivavyapashraya Chikitsa forms a key aspect in Ayurvedic treatment principles especially in Purvajanmakruta Karmaja Vyadhis (diseases resulting from past life deeds).…”
Section: Clinical Application: Punarjanmamentioning
confidence: 99%